Utilization of the Statistics Corner as a Source of Information: A Case Study of The Statistics Corner FEBI UINSU - Alya Tsabitah; Purwaningtyas, Franindya (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2024)
The library as an information agency will make it easier for users to find the various sources of information that they need. In order to facilitate users in searching for information in particular in the field of statistics, the library provides services in the statistical field, i.e. statistical corner service. The diversity in the use of the statistical corner makes this research aimed at finding out the utilization of the Statistical Corner as a source of information that is in FEBI UINSU as well as to know the opinion of users on the sources of information provided by the statistics corner of FEBI UINSU. This research uses qualitative descriptive methods with sampling using purposive techniques. Data collection techniques are done through observations and interviews. Then triangulation is done to find valid and credible research. The usage of this statistical corner is very varied in different places according to the needs of its users. In the statistics corner of FEBI UINSU usually uses the service to find out the statistical data he needs. The need for such statistical data is then exploited for a variety of purposes such as doing a lecture assignment, doing a final assignment or simply looking for additional information that could support their research.